Secure and resilient software development - Merkow, Mark S.; Raghavan, Lakshmikanth (CRC Press/An Auerbach Books, 2010)
Teaches you how to apply best practices and standards for consistent and secure software development. This title details specific quality software development strategies and practices that stress resilience requirements with precise, actionable, and ground-level inputs. It illustrates all phases of the secure software development life cycle